Experimental and Theoretical Investigations of Terahertz Spectra of the Structural Isomers: Mannose and Galactose - Zhang, Tongjun; Yan, Shasha; Hao, Jianjun; Li, Dehua (Journal of Spectroscopy, 2021)
The high-resolution terahertz spectra of the two structural isomers, mannose and galactose, have been measured by terahertz time-domain spectroscopy (THz-TDS) in the range of 0.5–4.0 THz at room temperature. Significant differences between these similar molecules have been found in their THz characteristic spectra, implying that THz-TDS is a powerful tool for identifying isomers. Structural analyses and normal mode calculations of the two systems were performed using solid-state density functional theory (DFT) with the PBE and PW91 density functionals as well as using gas-state DFT with B3LYP hybrid functional. Among these calculations, the solid-state simulated results obtained from the PBE method exhibit a good agreement with the experimentally measured spectra. According to the calculated results of PBE, the observed spectral features were assigned as primarily external lattice translations, deformations, and rotations with lesser contributions due to intramolecular motion of pyranose ring, CH2OH group, and hydroxyl groups.